(untitled) (Journal of Asian Development Studies, 2023)
Hemodialysis patients who adhere to a rigorous dialysis treatment plan, including dialysis, are prone to fatigue, which significantly influences their quality of life. Fatigue affects 60% to 97% of individuals with ESRD undergoing hemodialysis (HD). The study design was cross-sectional descriptive and was conducted in the Institute of Kidney Diseases Peshawar and Saidu Group of Teaching Hospitals from February to May 2023 using simple random sampling among 230 participants. The data was gathered using the Piper Short Scale-12, a valid and reliable tool with a reliability level of 0.87 to 0.89. Frequencies and percentages were used for categorical variables, and mean and standard deviation were used for continuous variables. Pearson correlation is used to calculate the relationship between demographic variables and fatigue using SPSS 20.0. In the current study, the maximum number of patients’ fatigue scores were moderate (67%), followed by severe fatigue (18%), while the remaining (13%) patient level of fatigue was low. In the moderate (36%) and extreme fatigue levels (10%), more patients are aged 18–35. The maximum mean score among the fatigue domains was behavioral (5.5 ± 1.1), while the overall mean score was 4.8 ± 0.95. The study concluded that most dialysis patients suffer from moderate fatigue, which is moderately positively correlated with marital status. At the same time, there is no correlation between fatigue with age and education and a mildly negative correlation with gender and employment. It is also established that individuals with end-stage renal disease (ESRD) have shown that fatigue is a significant problem that must be addressed to improve poor health outcomes and quality of life.